Digital Transformation in Local Tax Administration: A Study on Increasing Revenue through Online Payment in Nunukan Regency - Chaidir Maulana; Muliyadi Hamid; Nurmadhani Fitri Suyuthi (Jurnal Riset Perpajakan: Amnesty, 2026)
This study aims to examine the implementation of an online regional tax payment system in efforts to increase regional tax revenue at the Regional Revenue Agency (Bapenda) of Nunukan Regency, as well as to identify the supporting and inhibiting factors affecting the effectiveness of the system, particularly in remote areas. This research employs a descriptive qualitative approach, with data collected through in-depth interviews involving eight informants consisting of relevant government officials and taxpayers. The results indicate that the online payment system contributes positively to the increase in regional tax revenue, particularly in terms of time efficiency, ease of access, and the reduction of late payment risks. However, several technical challenges remain, such as limited internet connectivity in certain areas and the low level of digital literacy among some members of the community.Supporting factors for the effectiveness of this system include the commitment of the local government, technological support, and active community participation. Meanwhile, inhibiting factors consist of limited digital infrastructure, resistance among elderly citizens, and the lack of evenly distributed socialization. This study emphasizes the importance of a collaborative strategy among the government, financial institutions, and the community in optimizing an inclusive and sustainable online tax system.